ANALISIS KINERJA GURU PRODUKTIF DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PADA SMK NEGERI DI KOTA MAKASSAR - Khusnul Khatimah Jauharuddin; Muhammad Ardi; Muhammad Yahya (UNM Journal of Technology and Vocational, 2022)
This study aims (1) to describe the teachers’ performance in conducting learning at SMKN (public vocational schools) in Makassar city, (2) to identify work commitment, work attitude, work motivation, and principals’ leadership at several SMKN in Makassar city, (3) to analyze the influence of work commitment on the performance of productive teachers at SMKN in Makassar city, (4) to analyze the influence of work attitude on the performance of productive teachers at SMKN in Makassar city, (5) to analyze the influence of work motivation on the performance of productive teachers at SMKN in Makassar City, (6) to analyze the influence of the principals’ leadership on the performance of productive teachers at SMKN in Makassar city, and (7) to analyze the influence of work commitment, work attitude, work motivation, and the principals’ leadership collectively on the performance of teachers at SMKN in Makassar city. This type of research is quantitative research with a correlational approach. The research sample were 116 productive teachers at SMKN in Makassar city. The sampling technique employed a cluster random sampling technique. The analysisused were descriptive statistical analysis and inferential analysis of simple and multiple regression inferential models. The results of the study reveal that (1) the teachers’ performance are in high category; (2) there is a positive and significant influence of work commitment on teachers’ performance; (3) there is a positive and significant influence of work attitude on teachers’ performance; (4) there is a positive and significant influence of work motivation on teachers’ performance, (5) there is a positive and significant influence of the principals’ leadership on teachers’ performance; (6) there is a positive and significant influence of work commitment, work attitude, work motivation, and principals’ leadership collectively on teachers’ performance; and (7) there is a positive and significant influence of work commitment, work attitude, work motivation, and principals’ leadership collectively on teachers’ performance